Original paperTIME COURSE ALTERATIONS OF SATELLITE CELL EVENTS IN RESPONSE TO LIGHT MODERATE ENDURANCE TRAINING IN WHITE GASTROCNEMIUS MUSCLE OF THE RAT - Cai, Z.Y.; Hsu, C.C.; Hsu, M.C.; Huang, M.C.; Yang, C.P.; Lee, S.L.; Lin, W.C.; Su, B. (Biology of Sport, 2012)
This study investigated satellite cells and their related molecular events adapted to light moderate endurance training in the white gastrocnemius muscle of the rat. The white gastrocnemius muscle of male Sprague-Dawley rats that had been trained for 4 weeks and 8 weeks, with control rats being analysed alongside them, was selected for analysis (n=3 per group). The training protocol consisted of treadmill running at 20 m · min-1 for 30 min on a 0% grade, for 3 days · week-1. Immunohistochemical staining coupled with image analysis was used for quantification. To provide deeper insight into the cell layer, 40 sections per rat, corresponding to 120 values per group, were obtained as a mean value for statistical comparison. The results indicated that at week 4, training effects increased the vascular endothelial growth factor (VEGF) content and c-met positive satellite cell numbers. At week 8, the training effect was attenuated for VEGF and c-met satellite cell numbers, but it increased in the muscle fibre area. Additionally, c-met positive satellite cell numbers correlated with VEGF content (r = 0.79, p<0.05). In conclusion, this study suggests that light moderate endurance training could stimulate satellite cell activation that might be related to VEGF signalling. Additionally, the satellite cells activated by moderate endurance training might contribute to slight growth in myocytes.